User perception of mobile homes for shelter relief center as a respond for flood disaster preparednes - Abdul Rahim, Asiah; Zen, Ismawi; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Abdullah,, Che Zulkhairi; Abd. Samad, Nur Amirah (2016)
This reseqrch focuses on the effectiveness of proposed mobile homes for ihe flood relief center provision. The greot flood thoJ occurred in Moloysio hos reveoled o lock of recognition ond sofety procedures in hondling ond locoting viclims including people with disobiliiies ond the elderly. Most of the emergency shelter wos identified non universol ond inoccessible. The reseorch gops ideniified on existing focilities ore locking in privocy, sofely ond securily. The meihods of dolo collection will ocquire the primory doto which will be obioined from interviews, observolion, video recordings ond questionnoire. Secondory doto will be obloined from literoture, internet ond other reloled ogencies. Doto will be onolysed in order to identify the level of user perceplion, occeptonce of users ond relevonce of using corovons ond mobile homes for shelier relief cenire in Moloysio. This poper on design of mobile homes will conclude lhot ihe design should be efficient, provide privocy for the users, eosily conslruc+ed, lronsporfed by rood, oir ond boot ond reody-mode to coier the needs of viciims during flood disoster.